Analisis Molekuler Regio Pre-S1, Pre-S2, dan S Isolat Virus Hepatitis B 09IDSKAB-3 - Prasetyo, Angga Dwi; Prasetyo, Afiono Agung; Sari, Yulia (Nexus Biomedika, 2013)
Background: The Hepatitis B Virus (HBV) pre-S1, pre-S2, and S region are essentially known for virus infection and replication. Eight genotypes (A to H) and nine subtypes (adw2, adw4, ayw1, ayw2, ayw3, ayw4, adrq+, adrq-, and ayr) of HBV have been identified worldwide. The aim of this study was to analyze HBV genetic variation in pre-S1, pre-S2, and S region, and to determine genotype and subtype of 09IDSKAB-3 HBV isolate from Men Who Have Sex With Men community in Surakarta. Methods: 09IDSAKAB-3 HBV DNA extraction was used as a template for amplication of pre-S1, pre-S2, and S region. The sequence results were then aligned by Clustal W with all of reference sequences reported in GenBank/DDBJ/EMNL. Genetic variation in pre-S1, pre-S2, and S region were identified using MEGA 4.0. HBV genotype and subgenotype were identified by phylogenetic analysis. HBV subtype was deduced on the basis of the predicted amino acid sequences of HBsAg. Results: Based on BLAST search in GenBank, 09IDSKAB-3 isolate was classified into genotype B3. D27E variation was found in pre-S1 region, and there were not genetic variation in pre-S2 and S region. Phylogenetic tree showed that 09IDSKAB-3 isolate was classified into genotype B3. Based on the basis of predicted amino acid sequences of HBsAg, 09IDSKAB-3 isolate was classified into subtype adw2. Conclusions: Overall, only D27E variation was found in this study. 09IDSKAB-3 isolate was classified into genoytpe B3 and subtype adw2. The amino acid variations found in the present report need further study. Keywords: HBV, pre-S1 region, pre-S2 region, S region